PEMBAYARAN UPAH PEKERA PADA PERUSAHAAN YANG DINYATAKAN PAILIT - Ririn Pradnyandari, Ida Ayu; Sukihana, Ida Ayu; Dharmakusuma, A. A. Gede Agung (Kertha Semaya : Journal Ilmu Hukum, 2013)
Employees or workers are the driving forces of a business entity incorporated in a company’s management, which means without employees or workers, a company may not be able to conduct its business operations achieve company objectives to gain profit. Position of the workers in a company should be clear and also the process of the payroll payments, especially in the bankrupt company. In such cases the necessary normative method in which this method to analyze issues from a legal perspective that is based on the laws and regulations in force. workers' status and the payroll payment of a bankrupt company has the privilege where the payroll payment shall be paid in accordance with the salary that they should receive.
Keywords: Payment, Pay, Employee, Bankcrupt